The case against education : why the education system is a waste of time and money - Caplan, Bryan [Verfasser] (Princeton Univ. Press, 2018)
"Despite being immensely popular - and immensely lucrativ - education is grossly overrated. In this explosive book, Bryan Caplan argues that the primary function of education is not to enhance students' skill but to certify their intelligence, work ethic, and conformity - in other words, to signal the qualities of a good employee. Learn why students hunt for easy As and casually forget most of what they learn after the final exam, why decades of growing access to education have not resulted in better jobs for the average worker but instead in runaway credential inflation, how employers reward workers for costly schooling they rarely if ever use, and why cutting education spending is the best remedy. Caplan draws on the latest social science to show how the labor market values grades over knowledge, and why the more education your rivals have, the more you need to impress employers. He explains why graduation is our society's top conformity signal, and why even the most useless degrees can certify employability. He advocates two major policy responses. The first is educational austerity. Government needs to sharply cut education funding to curb this wasteful rat race. The second is more vocational education, because practical skills are more socially valuable than teaching students how to outshine their peers." (Publisher, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.3.2 Nordamerika; Bildungssystem; Bildungspolitik; Kritik; Kompetenzentwicklung; USA